MANAJEMEN PEMERINTAHAN DAERAH KABUPATEN KAMPAR DALAM MENGELOLA PASAR AIR TIRIS TAHUN 2008-2012 - Syarif, Yusrin; ", Hasanuddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
This research try to know Management Governance Of Area Sub-Province Camphor In Managing Market Irrigate Leak in the year 2008-2012. this Research type is research qualitative with descriptive method. In data collecting of researcher use observation technique, documentation and interview. By using informan key as source of information about this research.From result of obtained data finding that management of market Irrigate Leak in the year 2008-2012 society only involved in process of is forwarding of the problem of felt by society. Each Every activity doneconducted by Party side Organizer and of UPTD Regional of III Diawasai institutionally by Regent Camphor, and Inspectorate Sub-Province Camphor pass through On duty Industry market and commerce. In course of planning, involvement all institution cannot be discharged, because each every institution have its role each. Involvement all merchant in managing market Irrigate this Leak is involved in to know, diging and collecting information and also dig by seksama the problem of which they face so that to be fufilled of rights and obligations of merchant.In execution of management kewenangan and execution institution in Regional UPTD of III Market Irrigate Leak there are him weakness of execution of governance management where in management pemerinthan of good area have to base on performance. Known here still lower participation him all merchant in organization, as well as less intertwining of good cooperation among intansi in concerned in management of market Irrigate Leak. In execution of planning impementasi which have there is still burdened, because of extension of this market areal not yet owned to access good road;street. Knowable because lack of accessing this road street pursue process evacuation of merchant which is roadside berjualan of ketempat new. Observation process internally tehadap management of market Irrigate Leak done conducted by organizational unit in governance of itself area. Evaluate to peformance of is official member of market Irrigate Leak and of UPTD Regional of III done conducted by on duty Industry Commerce and Market.Keyword : Management Of Market Irrigate Leak, Participation in Organizational Perencanaan,Koordinasi anta in concerned in Management of market Irrigate Leak, Implementation of Planning